2021
DOI: 10.1002/aoc.6272
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of palladium nanoparticles: Preparation, characterization, and investigation of antioxidant, antimicrobial, anticancer, and DNA cleavage activities

Abstract: Green synthesis is considered to be one of the most suitable method because it enhances the therapeutic effects of palladium nanoparticles (Pd NPs). In this study, various biological activities such as antimicrobial, anticancer, antioxidant, and DNA cleavage activities of Urtica-mediated green synthesizing Pd NPs were investigated. The synthesized Pd NPs were characterized by using UV-vis, XPS, FT-IR, TEM, and XRD analyses. As a result of the TEM analysis of Pd NPs, the mean particle size was found to be 7.44 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Frontiers in Nanotechnology frontiersin.org activity against Callasobruchus maculates agricultural pest (Elango et al, 2017). At the same time, other biogenic Pd NPs exhibited anticancer activity, as those produced by Evolvulus alsinoides leaf extract, which were efficient against A2780 ovarian cancer cells (Gurunathan et al, 2015), and the NPs produced by Urtica, which were efficient against MDA-MB-231 human breast cancer cells, HT-29 human colon cancer cells, and MIA PaCa-2 human pancreatic cancer cells (Gulbagca et al, 2021). Some biogenic Pd NPs displayed a wide range of activities.…”
Section: Applications In Medicine Based On Toxic Effects Of Npsmentioning
confidence: 99%
“…Frontiers in Nanotechnology frontiersin.org activity against Callasobruchus maculates agricultural pest (Elango et al, 2017). At the same time, other biogenic Pd NPs exhibited anticancer activity, as those produced by Evolvulus alsinoides leaf extract, which were efficient against A2780 ovarian cancer cells (Gurunathan et al, 2015), and the NPs produced by Urtica, which were efficient against MDA-MB-231 human breast cancer cells, HT-29 human colon cancer cells, and MIA PaCa-2 human pancreatic cancer cells (Gulbagca et al, 2021). Some biogenic Pd NPs displayed a wide range of activities.…”
Section: Applications In Medicine Based On Toxic Effects Of Npsmentioning
confidence: 99%
“…Moreover, recent papers revealed that Pd nanoparticles obtained through a plantmediated biogenic approach are less toxic and biocompatible [33] and present important activity as an antioxidant, anticancer, antimicrobial and antiproliferative [9,10,12,[34][35][36][37][38][39][40][41][42][43][44], and can be used for environmental remediation [45]. Recent examples of the green synthesis of Pd nanoparticles mediated by plant extracts and their application as catalysts are shown in the Table 1.…”
Section: Plant Extractsmentioning
confidence: 99%
“…Thereafter, loading dye (0.25% bromphenol blue, 50% glycerol) was mixed into the reaction solution. The resulting mixtures were carried out on an electrophoresis gel using 0.8% agarose gel in TAE buffer (50 mM Tris base, 50 mM acetic acid, 2 mM EDTA, pH: 7.8) at 50 V [54].…”
Section: Dna Cleavage Activity Of Ag-ago-ag 2 O Nanocompositesmentioning
confidence: 99%